2004
DOI: 10.1002/app.21174
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of ethylene vinyl acetate copolymer (EVA)/natural rubber (NR) blend based foam

Abstract: ABSTRACT:In this study an attempt was made to improve the rebound resilience and to decrease the density of ethylene-vinyl acetate copolymer (EVA) foam. For this purpose, EVA was blended with natural rubber (NR), and EVA/NR blends were foamed at 155°C, 160°C, and 165°C. To investigate the correlation between crosslinking behavior and physical properties of foams, crosslinking behavior of EVA/NR blends was monitored. The physical properties of the foams were then measured as a function of foaming temperatures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 3 publications
0
34
0
1
Order By: Relevance
“…The melt processing of EVA was performed using a HAAKE minilab, which combines key features of batch mixers, twin-screw extruders, and rheometers. A series of specimens with variant processing time (5,15,20,25,30, and 35 min) were processed at 200°C, 50 rpm in HAAKE minilab. And all samples for dynamic mechanical analysis (DMA) and positron annihilation lifetime spectroscopy (PALS) analysis were obtained on a microinjection molding machine (Thermo Electron Corp.).…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The melt processing of EVA was performed using a HAAKE minilab, which combines key features of batch mixers, twin-screw extruders, and rheometers. A series of specimens with variant processing time (5,15,20,25,30, and 35 min) were processed at 200°C, 50 rpm in HAAKE minilab. And all samples for dynamic mechanical analysis (DMA) and positron annihilation lifetime spectroscopy (PALS) analysis were obtained on a microinjection molding machine (Thermo Electron Corp.).…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…Attarian et al 2 reported that the viscosity is expressed in familiar Arrhenius form with constant activation energy, whose value depends on the chemical structure of the polymer blend. Kim et al 5 studied the correlation between crosslinking behavior and physical properties of foams.…”
Section: Introductionmentioning
confidence: 99%
“…Natural rubber foam (NRF) is the sponge rubber that has been used in many industries due to its light weight, excellent thermal insulation, and sound absorption . Among several techniques to produce rubber foam , the addition of thermally decomposable chemical blowing agent is applicable for producing NRF specimen by the compression molding process because chemical blowing agent can be mixed with other compounding ingredients before shaping the rubber foam specimen in the mold.…”
Section: Introductionmentioning
confidence: 99%
“…Elastomeric foams are important in the man-made world; the reasons are both technical and commercial. From a tech-nical point of view, a variety of properties such as low density, chemical resistance and inertness, buoyancy, good aging, cushioning performance, thermal and acoustic insulation, and ability to be recycled, have ensured that polymeric foams have penetrated the automotive and transport, building and construction, marine, medical, sports, and leisure markets [3,4]. Fire hazards associated with the use of these polymeric foams, which result in the loss of life and property, are of particular concern among government regulatory bodies, consumers and manufacturers alike [1,2].…”
Section: Introductionmentioning
confidence: 99%